(untitled) (International Current Pharmaceutical Journal, 2014)
Tobacco use is widely spread throughout the world. The effect of smoking on human health are serious and in many cases, deadly. The present study was done to investigate the effect of cigarette smoking on some liver functions in male population in El-beida city, Libya. The study was carried out on thirty Libyan male smokers, who smoked at least 10 cigarettes per day for at least15 years. The group includes smokers with age range between 30-60 years. Non-smokers, (control, n= 30) group were collected with the same range of age for statistical comparison. The whole blood samples were drawn by venipuncture from each member and liver functions test were estimated by a kit method on automatic analyzer (Beckman BUN analyzer, USA). The results of the study revealed a significant increase of malondialdehyde (MDA), which is an indicator of lipid peroxidation and oxidative stress significantly increased in cigarette smokers in groups when compared with control group. While the plasma level of total protein, albumin and total bilirubin decreased during smoking. Cigarette smoking raised alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), plasma total cholesterol and triglycerides in smoker group when compared with non-smoker group. To conclude, cigarette smoking leads to oxidative stress by free radical generation by the mechanism of lipid peroxidation. Smoking exerts negative influence on liver functions test should be carefully interpreted, and further study on the mechanism of the effects is warranted. DOI: http://dx.doi.org/10.3329/icpj.v3i7.19077 International Current Pharmaceutical Journal, June 2014, 3(7): 291-295